Impact of oceanic gateway and CO2 changes on the East Asian summer monsoon during the mid-pliocene in a coupled general circulation model - Song, Zhaoyang; Zhang, Yuming (Frontiers in Environmental Science, 2022)
The Pliocene epoch from about 5.3 million to about 2.6 million years before present is the most recent period of sustained global warmth similar to the near future projections. The restriction of the Indonesian Passages, the closure of the Panama Seaway and declining atmospheric CO2-concentration are suggested to have caused the global climate evolution to the present-day condition. Here, we present the Pliocene sea surface temperature (SST) reconstructions along with sensitivity experimental results from a coupled General Circulation Model. We find that, in terms of SST, simulated model sensitivity to CO2 is in good agreement with the Pliocene reconstructions in most regions except the North Atlantic and Arctic. This suggests the necessity for improved boundary conditions and a possible underestimation of internal climate feedback at the high-latitudes. The responses of East Asian Summer Monsoon (EASM) to the oceanic gateway and CO2 are investigated. Influences of declining CO2 on the EASM are more prominent. An intensification of the intensity of EASM by ∼50% is simulated in response to the declining CO2, which is largely attributed to the strengthened land-ocean thermal contrast, while the precipitation decreases by ∼4.8%. In contrast, the restriction of two seaway changes only drives relatively weak changes with respect to wind speed and precipitation. A water vapor budget analysis suggests that the reduced atmospheric moisture content due to decreasing CO2 significantly contributes to precipitation response.